Wages and Employment in a Random Social Network with Arbitrary Degree Distribution. - Ioannides, Yannis Menelaos.; Soetevent, Adriaan R. (Tufts University. Tisch Library., 2016)
This paper shows analytically that workers who are better connected socially experience lower unemployment rates and receive higher wage rates in the average. It represents social connections in the labor market by a random graph, with nodes as individuals and edges as connections. The number of others each individual is connected with, the "degree," obeys an arbitrary probability distribution. In this fashion this paper extends previous research that in some cases assumes complete networks (everyone connected to everyone else) and in other cases balanced networks (everyone connected to an equal number of others)